Kajian Faktor yang Mempengaruhi Kemampuan Berpikir Kritis Perawat Klinis di Instalasi Rawat Inap - Tiarmaida Sitio; Asep Setiawan; Fauziah Rusdhiati (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the factors that influence the critical thinking skills of clinical nurses in performing nursing care at the inpatient installation of Immanuel Hospital, Bandung. The method used was an analytic survey with a cross-sectional design on 161 clinical nurses at the inpatient installation of Immanuel Hospital, Bandung. Data collection was carried out using a questionnaire which was then analyzed using the chi-square test and multiple logistic regression tests. The results showed that there was no significant relationship between nurse characteristics, motivation, anxiety, organization, health condition of nurses and critical thinking skills (p > 0.05), but there was a significant relationship between education (p = 0.009) and knowledge (p = 0.001 ) with critical thinking skills. In conclusion, two variables influence nurses' critical thinking skills, namely education and knowledge factors. Keywords: Nursing Care, Critical Thinking, Clinical Nurse